Prevalencia de demodicosis canina en la ciudad de Machala - Llanos Ortega, Gabriel Serafin (2010)
The present investigation took place in the City of Machala, the same one that was divided in six parishes in where a corresponding study was made to diagnose the Prevalence of canine demodicosis. As objective of this one investigation we had: To determine the prevalence of Canine Demodicosis in the City of Machala and Establish the presence of demodectic scabies according to the age, sex, race, taken care of the animal, type of lodging and zones of study. In order to take it shows them of a dog that presented/displayed problems of skin with tendency to scabies, was come with a leaf of bistourie dampened with a little from glycerin to make deep scraping until obtaining a light one bled, soon was come to place the sample obtained in a porthole object, soon to place a drop of glycerin and finally it covers object and it was come to observe the microscope with lens of 100 xs. As final result we have not they found positive cases in the obtained samples of dogs that had problems of skin with tendency to scabies in the six parishes destined for this one investigation, and information on the part of the proprietors of some dogs was obtained that we found healthy, that such they had suffered of diseases of the skin before, but already had been controlled by means of a strict veterinary control. It is possible to stress that by the fact not to have negative results one is going away to discard the presence of the disease within the City; also emphasis is made that the months in which the work of field lasted began in the middle of June until end of August, and during these months there was no the rain presence and he was escaza the humidity, which partly “favored” that they do not present/display in great amount problems of skin in the evaluated dogs.